Characters in Audio Visual-Based Teaching Materials in Thematic Learning in Elementary Schools - Beni Azwar; Deri Wanto; Yurika Nopianti (Institut Agama Islam Negeri (IAIN) Curup, 2022)
This scientific article is motivated by the lack of character in students, where as we know today's technological advances can make the character decline in students, but if technology is used properly there will be many benefits, where most students in Indonesia currently With gadgets, technological advances can have both positive and negative impacts. The purpose of this research is to instill the character of students through the use of audio-visual-based teaching materials, such as videos. This study uses a qualitative method with the type of library research (library research), while data collection uses documentation techniques, namely data collection or from books or literatures and journals that discuss